Plan de exportación de pasta de cacao para la unión cantonal de organizaciones de participación social por la justicica del cantón las naves (UCOCS)- prov bolivar hacia el mercado italiano año 2011 - Peralta Verdezoto, Ligia Esther (2011)
The organization is under the ownership of the subsidiary organizations that are directing, through the Directory, the social development, which are: Las Mercedes Association, Buenos Aires Association, Bellavista Association, Naveñitos en Acción Association, Las Naves Peasant Association, Trinidad Association Bonilla and recently joined the Interprofessional Association of Craftsmen "29 de Agosto", in which, over time they have remained as definitive owners of the Cantonal Union whose legal representative is Mr. Víctor Manuel Arana Sánchez, president of the organization of second grade. In turn, the Board of Directors (represented by the subsidiary organizations) has arranged as responsible for the current economic activity the Technologist César Franklin Castillo Castro who acts as Manager, of which, he is accompanied by the Engineer Leonardo Isidro Manobanda Calberto (accountant), Mr. Oswaldo Liborio Castillo Castro (coordinator), Mr. Jaime Darwin Intriago Ayosa (qualifier-bodeguero) and Mr. Vicente Emiliano Montoya Gil (warehouse assistant). The Cantonal Union is located on Gil Avilés Avenue, via Zapotal, in front of the construction of the Distance Education Unit of Bolívar "Monseñor Leonidas Proaño", Las Naves Extension, Las Naves canton, Bolívar province, Republic of Ecuador. The Cantonal Union of Organizations of Social Participation for Justice of the Las Naves canton is a private, nonprofit, second-tier organization that is currently engaged in the commercialization of cocoa at a fair price with a Rainforest Alliance Certification. it has allowed us to preserve a